USE OF INNOVATIVE COMPUTER TOOLS AND SCIENTIFIC RESEARCH METHODS IN THE FOOTWEAR INDUSTRY - ZLOTENKO, BORYS; VOLIANYK, OLEKSII; RUBANKA, MYKOLA; STATSENKO, DMYTRO; MELNYK, HENNADII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
An experimental setup based on a personal computer and an Arduino Uno microcontroller was developed to measure and record footwear pressure on the human foot during standing and walking. Comfortable pressure values exerted by footwear on the foot were determined to be within the range of 10.5 to 11.0 kPa. An innovative method for designing the internal shape of footwear was proposed, based on the results of 3D foot scanning and subsequent modification of the shoe last using 3D-printed pads tailored to the individual anatomical features of the user. A 3D printing technology was developed to create flexible soles for women’s sports shoes. Research was conducted on the physico-mechanical properties of polyethylene terephthalate glycol (PETG) specimens produced by 3D printing with varying infill densities. The values of tensile strength and relative elongation of the printed specimens were determined. The obtained data were used to calculate the parameters of a power law equation that describes the stress-strain relationship during tensile testing of the printed samples. To approximate the experimental tensile curves, the Ludwik power law was used, and the parameters K and n were calculated for different print densities. It was shown that with increasing infill density, the tensile strength increases while the relative elongation decreases, indicating strengthening of the internal structure of the material. Stress-strain diagrams were constructed for PETG samples with 60–100% infill density. The obtained results make it possible to predict the material’s behaviour under load and can be used in the design of polymer products manufactured by additive technologies to ensure their reliability, functionality, operational safety, and durability, as well as adaptation to individual usage conditions in various industrial applications.